2010
DOI: 10.1093/jnci/djq516
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the Jaw and the Role of Macrophages

Abstract: Nitrogen-containing bisphosphonates have been associated with the development of osteonecrosis of the jaws (ONJ), but the lack of reliable epidemiological data and appropriate animal models has restricted our understanding of ONJ pathophysiology and limited its management. The best available information is from histopathologic findings, which implicate bone necrosis and infection, although it is not clear which is primary. However, there are data suggesting that macrophages could well be the central factor in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(105 citation statements)
references
References 72 publications
4
101
0
Order By: Relevance
“…It has also been proposed that the adverse effects of nitrogen-containing bisphosphonates on macrophage viability may impair the immune response, acting on the mevalonate pathway to induce apoptosis [84,85]. Vitamin D deficiency is associated with reduced macrophage differentiation and decreased production of the antibacterial protein, cathelicidin, and may further suppress the response to infection [86].…”
Section: Altered Immune Statusmentioning
confidence: 99%
“…It has also been proposed that the adverse effects of nitrogen-containing bisphosphonates on macrophage viability may impair the immune response, acting on the mevalonate pathway to induce apoptosis [84,85]. Vitamin D deficiency is associated with reduced macrophage differentiation and decreased production of the antibacterial protein, cathelicidin, and may further suppress the response to infection [86].…”
Section: Altered Immune Statusmentioning
confidence: 99%
“…35) Thus, other factors-possibly, infection or impairment of the defense mechanisms against infection-might be the common, and most important, factor leading to the induction of ONJ by N-BPs and denosumab. 28,35,36) We previously reported that lipopolysaccharide (LPS), a potent inflammatory component of the cell walls of Gram-negative bacteria, augments both the production of the inflammatory cytokine IL-1 and the induction of the histamine-forming enzyme histidine decarboxyl- ase. 31,32) Possibly, such an increased production of IL-1 might act in conjunction with that induced by N-BPs (see above a-d).…”
Section: )mentioning
confidence: 99%
“…The direct toxic effects of bisphosphonates on oral mucosa can result in the ability of oral pathogens to pass through defective or severely damaged oral mucosa and infect the bone [120]. Clinically, gastrointestinal intolerability is one of the most recognisable side effects of oral preparations of nitrogen-containing bisphosphonates such as alendronate, risendronate and ibandronate.…”
Section: Direct Toxicity To Oral Mucosal Cellsmentioning
confidence: 99%